1998
DOI: 10.1016/s0038-1098(97)10154-5
|View full text |Cite
|
Sign up to set email alerts
|

Vortex contribution to specific heat of dirty d-wave superconductors: Breakdown of scaling

Abstract: We consider the problem of the vortex contribution to thermal properties of dirty d-wave superconductors. In the clean limit, the main contribution to the density of states in a d-wave superconductor arises from extended quasiparticle states which may be treated semiclassically, giving rise to a specific heat contribution δC(H) ∼ H 1/2 . We show that the extended states continue to dominate the dirty limit, but lead to a H log H behavior at the lowest fields, Hc1 < ∼ H ≪ Hc2. This crossover may explain recent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
163
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(172 citation statements)
references
References 21 publications
6
163
1
2
Order By: Relevance
“…(4),(5) still hold in the superclean limit where (∆Γ) 1 2 v √ eH with Γ denoting the quasiparticle scattering rate in the normal state [3,4]. There are only two energy scales in this limit, namely v √ eH and T. Therefore the thermodynamic functions obey the scaling law as proposed by Simon and Lee [26] and shown for a particular case by Kübert and Hirschfeld [19].…”
Section: The Volovik Effectmentioning
confidence: 82%
See 1 more Smart Citation
“…(4),(5) still hold in the superclean limit where (∆Γ) 1 2 v √ eH with Γ denoting the quasiparticle scattering rate in the normal state [3,4]. There are only two energy scales in this limit, namely v √ eH and T. Therefore the thermodynamic functions obey the scaling law as proposed by Simon and Lee [26] and shown for a particular case by Kübert and Hirschfeld [19].…”
Section: The Volovik Effectmentioning
confidence: 82%
“…Here ... means average over the Fermi surface and over the unit cell of the vortex lattice. In the present configuration this is readily done [2,19] …”
Section: The Volovik Effectmentioning
confidence: 99%
“…Overall, γ v (H) is better represented by the solid straight line, which has a slope 0.75 mJ K -2 mol -1 T -1 , than the dashed curve for H 1/2 . (The HlnH dependence suggested for a dirty d-wave superconductor 27 would not give a better fit.) For this reason, and particularly because the low-field data suggest a finite limiting slope, these results are more consistent with an isotropic gap than with the low-energy excitations associated with nodes.…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that this H 1/2 dependence is modified to HlnH at low fields in a dirty superconductor. 27 Modifications of the H-proportional dependence in the case of an isotropic gap, negative curvature in high fields, have also been suggested 28 . The H dependence of γ v (H) is compared with H and H 1/2 dependences in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This work has been extended into several directions: a) thermodynamic functions; b) thermal conductivity; c) scaling relations; d) for arbitrary field orientation; and e) for a variety of gap functions ∆(k) ′ s [14,15,16,17,18,19]. As is well known the gap symmetry and the gap function has been the central issue since the discovery of the heavy-fermion superconductors [20].…”
mentioning
confidence: 99%